2019
DOI: 10.3389/fonc.2019.00628
|View full text |Cite|
|
Sign up to set email alerts
|

Afatinib for Advanced Non-small Cell Lung Cancer in a Case With an Uncommon Epidermal Growth Factor Receptor Mutation (G719A) Identified in the Cerebrospinal Fluid

Abstract: Few previous studies of patients with non-small cell lung cancer (NSCLC) and leptomeningeal metastases have used liquid biopsy of cerebrospinal fluid (CSF) to identify epidermal growth factor receptor (EGFR) mutations and guide therapy. A 34-year-old male patient with NSCLC and leptomeningeal metastases was admitted to the Interventional Radiology Department, Tianjin Huanhu Hospital on 18th April 2018 after showing no response to chemoradiotherapy. On admission, the patient was in critical condition with an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Afatinib, a second generation EGFR-TKI, was approved by the U.S. FDA for metastatic NSCLC with uncommon non-drugresistant EGFR mutations, such as L861Q, G719X, and S768I. Afatinib can achieve half maximal inhibitory concentration (IC50) against EGFR mutation in the cerebrospinal fluid [13] so that theoretically it can create an inhibitory effect on intraventricular metastases from lung cancer with minimal adverse effects. Molecular analysis indicated EGFR mutation (G719X) in this patient and both lesions in bilateral lungs and brain showed significant improvement after treatment with afatinib, which supported that the intraventricular lesions were metastatic disseminations of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Afatinib, a second generation EGFR-TKI, was approved by the U.S. FDA for metastatic NSCLC with uncommon non-drugresistant EGFR mutations, such as L861Q, G719X, and S768I. Afatinib can achieve half maximal inhibitory concentration (IC50) against EGFR mutation in the cerebrospinal fluid [13] so that theoretically it can create an inhibitory effect on intraventricular metastases from lung cancer with minimal adverse effects. Molecular analysis indicated EGFR mutation (G719X) in this patient and both lesions in bilateral lungs and brain showed significant improvement after treatment with afatinib, which supported that the intraventricular lesions were metastatic disseminations of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [ 13 ] reported on the efficacy of afatinib treatment in a patient with NSCLC and a non-classical EGFR mutation (G719A). Frega et al [ 8 ] have also reported on the response to afatinib treatment of a patient with NSCLC carrying 3 non-classical mutations: exon 18 E709K and an exon 21 L833V_H835L complex mutation.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there have been more studies investigating CSF ctDNA in LM than in BM, although patient numbers remain overall small, in part due to the rarity of this disease. Similarly to BM, some case reports detail successful treatment changes in response to mutations detected in CSF ctDNA [ 44 , 52 ], and a few studies report a similar correlation between CSF ctDNA levels and disease status, with increases at the time of progression and decreases in response to treatment [53] , [54] , [55] . Moreover, CSF ctDNA has been explored as a prognostic tool in LM, with a few studies in NSCLC showing a correlation between CSF ctDNA levels and presence of specific genomic alterations and survival [ 35 , 56 , 57 ].…”
Section: Circulating Tumor Dna (Ctdna)mentioning
confidence: 99%